Her fearful symmetry : a novel - Niffenegger, Audrey (New York : Scribner, 2009)
The twins hope that in London their own, separate, lives can finally begin but they have no idea that they've been summoned into a tangle of fraying lives, from the obsessive-compulsive crossword setter who lives above them to their aunt's mysterious and elusive lover who lives below them and works in the cemetery itself.
Keywords: Sisters -- Fiction; Psychological fiction